Promosi Kesehatan Daun Katuk Untuk Peningkatan Produksi Asi Terhadap Pengetahuan Ibu Nifas - Kuhu, Fonnie Fonnie; Purba, Relyana; Tombokan, Sandra G.J.; Lontaan, Anita; Adam, Yulin; Lumy, Freike S.N; Donsu, Amelia; Lalita, EMF (POLTEKKES KEMENKES MANADO, 2022)
Background : Failure to give breast milk by the mother, among others, the mother feels tired due to the delivery process, the milk does not come out, the milk production is low, or the mother reasons that she has never given exclusive breastfeeding. Katuk leaves (Sauropus Androgynus L'Merr) is a lactagogue plant that can increase milk production. Purpose : Knowing the effect of health promotion of katuk leaves to increase milk production on the knowledge of postpartum mothers in the Kauditan Health Center, North Minahasa Regency. Method : This research design uses the method Quasi-experimental design with a one-group pretest-posttest to compare before and after the experiment was carried out with 33 samples, taking samples by means of non-probability sampling. Data collection used a questionnaire containing a number of written questions. The experiment used counseling methods for postpartum mothers. Data analysis used the Wilcoxon test with significance. Results : shows that health promotion of katuk leaves to increase milk production can affect the knowledge of postpartum mothers in the working area of ​​the Kauditan Health Center, North Minahasa Regency. Recommendations for postpartum mothers can apply by consuming katuk leaves to help increase milk production.